Kajian Kondisi Terumbu Karang dan Strategi Pengelolaannya di Pulau Panjang, Air Bangis, Kabupaten Pasaman Barat - Oktarina, Angreini; Kamal, Eni; Suparno, Suparno (Jurnal Natur Indonesia, 2014)
Coral reef ecosystems are essential for the survival of marine life, but the presence of coral reef are declined and decayed.Methods used in this study was a survey method. To retrieve the condition of coral cover using the line intercept transectwhile to determine management strategies using SWOT analysis. The average percentage of coral cover in 8 point researchstations at 50.10% are still in the good condition, which is in the north 3 m depth 53.51%, north 7 m depth 68.14%, east 3 mdepth 93.29%, east 7 m depth 15.93%, south 3 m depth 75.17%, south 7 m depth 20.53%, west 3 m depth 41.50%, and west7 m depth 32.79%. The strategies for coral reef ecosystem management, among others: 1) community-based management, 2)forming Kelompok Masyarakat Pengawas (Pokmaswas) institutions, 3) establish in Panjang Island as a marine conservationareas, 4) Ko-Management-based, 5) effort to improve the economy in order to support the increased knowledge of theimportance of conservation and management of coral reef ecosystem.